2005
DOI: 10.1017/s0959270905000067
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of extinction: population decline in the colonially nesting Tricolored Blackbird Agelaius tricolor

Abstract: Tricolored Blackbird Agelaius tricolor is a rapidly declining species largely endemic to California and forms larger breeding colonies than any other extant North American landbird following the extinction of Passenger Pigeon Ectopistes migratorius. We present information on its distribution, breeding habitat and changes in global population size using data collected since the 1930s. We also present data on reproductive success at 103 colonies between 1992 and 2003. While possibly once the most abundant bird t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…Our observed changes in populations in different regions and habitats are consistent with Beedy et al (1991) and Cook and Toft (2005). Himalayan blackberry sites showed slower declines in average colony size than other habitats, and cattail sites declined in average colony size more rapidly than other habitats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our observed changes in populations in different regions and habitats are consistent with Beedy et al (1991) and Cook and Toft (2005). Himalayan blackberry sites showed slower declines in average colony size than other habitats, and cattail sites declined in average colony size more rapidly than other habitats.…”
Section: Discussionsupporting
confidence: 92%
“…Himalayan blackberry and thistles also represent nonnative invasive species, so we are left with a conundrum of needing to protect areas of an invasive species to protect tricolored blackbird colonies (Cook and Toft 2005). Furthermore, over 50% of the breeding population in any given year was within relatively few triticale farm field colonies, requiring protection of these in at least the short term for conservation of this species.…”
Section: Discussionmentioning
confidence: 99%
“…parasite load that may change over time; Boulinier, McCoy, & Sorci, 2001; Danchin, 1992), past familiarity with the habitat around a site, and the number of conspecifics potentially or actually present (the colony size expectation with the associated costs and benefits of grouping; Brown & Brown, 1996) in deciding whether to be philopatric or disperse to a new colony site (Bonte et al, 2012). Knowing how colonial individuals make the decision to stay or go is critically important, both for understanding the metapopulation dynamics of colony occupancy (which may explain population-wide colony size variation; Johst & Brandl, 1997; Matthiopoulos, Harwood, & Thomas, 2005; Russell & Rosales, 2010) and for understanding how colonial species of conservation concern become ‘trapped’ in a subset of available colony sites (Cook & Toft, 2005; Kenyon, Smith, & Butler, 2007; Schippers, Stienen, Schotman, Snep, & Slim, 2011) due to their reluctance to disperse to new sites.…”
mentioning
confidence: 99%
“…We previously showed that long-term (1930's to 1980's) trends in the average size of breeding colonies (numbers of birds) varied both among geographical regions and nesting substrates [7]. Cook and Toft [15] also reported that reproductive success (number of 7–9 day old chicks per nest) was greater for colonies nesting in Himalayan blackberry than for those in native cattail or tule marshes. Additionally, silage colonies had low average reproductive success because of harvest before young birds fledged [15].…”
Section: Introductionmentioning
confidence: 99%